2010
DOI: 10.1088/0004-637x/715/2/1508
|View full text |Cite
|
Sign up to set email alerts
|

Massive Halos in Millennium Gas Simulations: Multivariate Scaling Relations

Abstract: The joint likelihood of observable cluster signals reflects the astrophysical evolution of the coupled baryonic and dark matter components in massive halos, and its knowledge will enhance cosmological parameter constraints in the coming era of large, multi-wavelength cluster surveys. We present a computational study of intrinsic covariance in cluster properties using halo populations derived from Millennium Gas Simulations (MGS). The MGS are re-simulations of the original 500 h −1 Mpc Millennium Simulation per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

58
256
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(317 citation statements)
references
References 102 publications
58
256
2
1
Order By: Relevance
“…The main difficulty that simulation methods face is our incomplete understanding of baryonic physics, particularly galaxy formation feedback processes. These difficulties can be minimized by defining new X-ray observables that are expected to be robust to these details, and through careful exploration of the sensitivity of the observable-mass relation to the physics that goes into the simulations (e.g., Nagai et al, 2007;Rudd and Nagai, 2009;Stanek et al, 2010;Fabjan et al, 2011;Battaglia et al, 2012). The simulations themselves are steadily improving thanks to increased computer power, more sophisticated algorithms, and the availability of better data to test the input physics.…”
Section: Calibrating the Observable-mass Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difficulty that simulation methods face is our incomplete understanding of baryonic physics, particularly galaxy formation feedback processes. These difficulties can be minimized by defining new X-ray observables that are expected to be robust to these details, and through careful exploration of the sensitivity of the observable-mass relation to the physics that goes into the simulations (e.g., Nagai et al, 2007;Rudd and Nagai, 2009;Stanek et al, 2010;Fabjan et al, 2011;Battaglia et al, 2012). The simulations themselves are steadily improving thanks to increased computer power, more sophisticated algorithms, and the availability of better data to test the input physics.…”
Section: Calibrating the Observable-mass Relationmentioning
confidence: 99%
“…While an overall shift in the normalization of the multi-variate observable-mass relation P (X 1 , X 2 |M ) is still degenerate with cosmology, the addition of the clustering signalwhich depends on cluster masses directly -allows one to jointly calibrate P (X 1 , X 2 |M ) while still improving the cosmological constraints relative to those derived from a single observable (Cunha, 2009). The improvement is driven by the fact that using two cluster observables simultaneously allows one to better constrain the scatter of the observable-mass relation (see also Stanek et al, 2010). Given the large overlap between many of the currently ongoing or near future cluster surveys (e.g., DES fully overlaps with SPT), we expect this type of analysis to become increasingly important in the coming decade.…”
Section: Calibrating the Observable-mass Relationmentioning
confidence: 99%
“…Stanek et al (2010) presented a computational study of the intrinsic covariance of cluster observables using the Millennium Gas Simulations. Two different physical treatments were proposed: shock heating driven by gravity only, or a second treatment with cooling and preheating.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Stanek et al (2010) found that the evolution with redshift might be negative (γz ∼ −0.34) in presence of cooling and preheating. In agreement with simulations, we did not detect any departure from the self-similar scaling, with βY -Z = 1.50 ± 0.21.…”
Section: Ysz-m∆mentioning
confidence: 99%
See 1 more Smart Citation